Sustainable Manhattan 2050: visions for resilient community in the age of peak oil and climate destabilization - Coates, Gary (Kansas State University, 2011)
It is becoming increasingly clear that the 21st century will constitute a radically new era in human history, one that will be defined by our collective response to three inescapable and interconnected problems that are already combining to create a perfect storm: The Population Explosion: The global population now stands at 6.7 billion people. By 2050 it is estimated that there will be more than 9 billion. Peak Oil and Natural Gas: There is a growing concensus among petroleum geologists and that we are presently on the “bumpy plateau” of peak oil and that the era of easily accessible, cheap oil (and other fossil fuels) is now forever behind us. With almost unimaginable consequences, it is estimated that by 2030 the world will have approximately 25% less oil than is currently available and 50% less by the year 2050. Climate Destabilization, Mass Extinctions and Ecosystem Collapse: As a direct result of population pressures and human activity we are already living in an era scientists call the Sixth Great Extinction. Without rapid and dramatic action to limit the production of greenhouse gases it is virtually certain that we will cross key climate change tipping points, leading to a world that is seriously inhospitable to all life as we know it. In order to respond effectively to these pressing problems it will be necessary for us to literally remake the human footprint on the earth, town by town and community by community. Our goal must be to create a sustainable pattern of human settlements comprised of compact, socially diverse, pedestrian-scaled and livable eco-communities that integrate renewable energy production, urban design, transportation planning, climatically adapted architecture, organic agriculture and ecologically based land use planning. The design of such resilient human ecologies, which would have to be carefully and gracefully integrated within the naturally occurring ecosystems of which they are a part, constitutes both the means and the ends of the great transformation that lies ahead. The land grant university is uniquely suited, in terms of its history, purpose and founding vision, to provide the societal guidance necessary in order to make the transition to a sustainable society worth sustaining. In order to demonstrate how Kansas State University can become a leader in the movement to create a sustainable pattern of human settlements, this presentation provides an overview of a graduate architectural design studio aimed at creating a resilient and sustainable Manhattan by the year 2050. During the fall semester of 2010 students developed a phased master plan for Manhattan and the surrounding area that is built around a multi-modal transportation system comprised of bikeways, walking paths, streetcars and roads for electric buses and autos. Within this framework students in the second semester will design specific areas of the city that are most critical in meeting the sustainability goals of the class. This presentation will provide a brief overview of these projects, which are presented in more detail by the students themselves in posters prepared for this conference. 1) Sustainable Manhattan 2050: Master Plan based on a Multi-Modal Transportation System 2) Flint Hills Place: A Green Downtown Urban District 3) Fort Riley Boulevard: The Transition to an Urbane Mixed-Use Streetcar Avenue 4) Poyntz Avenue Housing: Adaptive re-use of Existing Historical Architecture 5) Near Net Zero Energy Backhouses, Granny Flats and Garage Apartments: A Strategy for Increasing Density and Sustainability in the Older Neighborhoods 6) The North End Mixed-Use Eco-community: A Case Study in Sprawl Repair and Integrated Community Development 7) Kimball Avenue Eco-village: Agricultural Urbanism as a Context for Organic and Sustainable Agriculture As Buckminister Fuller once said, “The best way to predict the future is to design it.” The design of resilient cities, such as the sustainable Manhattan envisioned by our studio for the year 2050, constitutes both the means and the ends of the great transformation that lies ahead. The purpose of sharing our design and planning studies of what Manhattan might look like in the coming age of Peak Oil and Climate Destabilization is to begin a dialogue about the role of Kansas State University in helping to make the transition to a resilient and sustainable society.
Keywords: Eco-communities; Oil; Urbanism; Natural gas; Climate; Population; Ecosystems; Mass extinctions